Segmentation and mechanical characterization of atherosclerotic plaques - Latorre Molins, Álvaro Tomás; Peña Baquedano, Estefanía; Cilla Hernández, Myriam; Martínez Barca, Miguel Ángel (Jornada de Jóvenes Investigadores del I3A, 2022)
Detection and mechanical characterization of atheroma plaques are vital steps for an early diagnosis of vulnerable patients. In coronary artery, Intravascular Ultrasound is the gold standard for visualizing the arterial wall. In combination with new technologies it is possible to estimate the arterial strains. In this work we have developed a new methodology to segment and obtain the mechanical properties of atheroma plaque tissues.